An exploratory randomized control study of combination cytokine and adult autologous bone marrow progenitor cell administration in patients with ischaemic cardiomyopathy: the REGENERATE‐IHD clinical trial. (28th October 2016) - Choudhury, Tawfiq; Mozid, Abdul; Hamshere, Steve; Yeo, Chia; Pellaton, Cyril; Arnous, Samer; Saunders, Natalie; Brookman, Pat; Jain, Ajay; Locca, Didier; Archbold, Andrew; Knight, Charles; et al.
Abstract: Aims: The effect of combined cytokine and cell therapy in ischaemic cardiomyopathy is unknown. Meta‐analyses suggest improved cardiac function with cell therapy. The optimal cell delivery route remains unclear. We investigated whether granulocyte colony‐stimulating factor (G‐CSF) alone or in combination with intracoronary (i.c.) or intramyocardial (i.m.) injection of autologous bone marrow‐derived cells (BMCs) improves cardiac function. Methods and results: Ninety patients with symptomatic ischaemic cardiomyopathy and no further treatment options were enrolled in the randomized, placebo‐controlled, single‐centre REGENERATE‐IHD study. Randomization was to one of three arms: peripheral, i.c., or i.m. In each arm, patients were randomized to active treatment or placebo. All patients, apart from the peripheral placebo group (saline only) received G‐CSF for 5 days. The i.c. and i.m. arms received either BMCs or serum (placebo). The primary endpoint was change in LVEF at 1 year assessed by cardiac magnetic resonance imaging/computed tomography. The i.m. BMC group showed a significant improvement in LVEF of 4.99% (95% confidence interval 0.33–9.6%; P = 0.038) at 1 year. This group also showed a reduction in NYHA class at 1 year and NT‐proBNP at 6 months. No other group showed a significant change in LVEF. This finding is supported by post‐hoc between‐group comparisons. Conclusion: We have shown that G‐CSF combined with autologous i.m. BMCs has a beneficial effect on cardiac function and symptoms. However, this result should be considered preliminary in support of a clinical benefit of i.m. stem cell infusion in 'no option' patients and needs further exploration in a larger study.